2005
DOI: 10.1523/jneurosci.3045-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Propagation of Simple and Complex Spikes in Cerebellar Purkinje Neurons

Abstract: In cerebellar Purkinje neurons, the reliability of propagation of high-frequency simple spikes and spikelets of complex spikes is likely to regulate inhibition of Purkinje target neurons. To test the extent to which a one-to-one correspondence exists between somatic and axonal spikes, we made dual somatic and axonal recordings from Purkinje neurons in mouse cerebellar slices. Somatic action potentials were recorded with a whole-cell pipette, and the corresponding axonal signals were recorded extracellularly wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
158
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(178 citation statements)
references
References 68 publications
18
158
2
Order By: Relevance
“…Innervation of single DCN neurons by multiple Purkinje neurons is likely crucial for the alterations reported here to be consequential for the DCN firing given that, in individual neurons, axonal propagation of action potentials, particularly of spikelets, which are more often of stout stature, is unreliable at the high frequencies attained within complex spikes (Khaliq and Raman, 2005;Monsivais et al, 2005). Intriguingly, Kv3.3 channels thus far appear not to be enriched at nodes of Ranvier, in contrast to Kv3.1 (Chang et al, 2007), offering a potential explanation for the conduction failures and suggesting this is not the subcellular locus of Kv3.3 function.…”
Section: Perturbed Complex Spikes: Potential Impact On Deep Nuclear Nmentioning
confidence: 92%
“…Innervation of single DCN neurons by multiple Purkinje neurons is likely crucial for the alterations reported here to be consequential for the DCN firing given that, in individual neurons, axonal propagation of action potentials, particularly of spikelets, which are more often of stout stature, is unreliable at the high frequencies attained within complex spikes (Khaliq and Raman, 2005;Monsivais et al, 2005). Intriguingly, Kv3.3 channels thus far appear not to be enriched at nodes of Ranvier, in contrast to Kv3.1 (Chang et al, 2007), offering a potential explanation for the conduction failures and suggesting this is not the subcellular locus of Kv3.3 function.…”
Section: Perturbed Complex Spikes: Potential Impact On Deep Nuclear Nmentioning
confidence: 92%
“…The development of tight-seal axonal bleb recording was inspired by extracellular loose-patch recordings from the axons of cerebellar Purkinje cells [34,35] . Because of the surrounding myelin sheath, the membrane of axonal blebs was not accessible to patch pipettes and thus only extracellular spikes were detectable.…”
Section: Applications Of Axonal Bleb Recordingmentioning
confidence: 99%
“…Because of the surrounding myelin sheath, the membrane of axonal blebs was not accessible to patch pipettes and thus only extracellular spikes were detectable. Using this axonal loose patch technique, two research groups [34,35] found that somatic simple spikes are faithfully transmitted along the axons of Purkinje cells, whereas the complex spike waveform cannot be faithfully propagated to distal axonal compartments.…”
Section: Applications Of Axonal Bleb Recordingmentioning
confidence: 99%
“…In extracellular recordings of action potentials from axons of hippocampal CA3 pyramidal neurons, the maximum rate of reliable propagation of APs was ϳ160 Hz (Raastad and Shepherd, 2003;Meeks et al, 2005). In Purkinje cell axons, simple spikes propagated with a high success rate at up to 200 Hz but became unreliable at 300 Hz (Khaliq and Raman, 2005;Monsivais et al, 2005). Thus, in comparison with other classes of neurons in which high-frequency action potential propagation has been examined, granule cells are remarkable in their ability to reliably signal at up to 500 Hz.…”
Section: Reliability Of Axonal Signaling At High Frequencymentioning
confidence: 99%